Toward a new microfounded macroeconomics in the wake of the crisis - Eugenio Caverzasi; Alberto Russo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
The Great Recession that followed the financial crisis of 2007 is not only the largest economic crisis after the Great Depression of the 1930s, it also signals a crisis of economics as a discipline. This is not only the consequence of the inadequacy of mainstream macroeconomics, and specically the DSGE workhorse model, to forecast such a huge event, or at least to detect the worrying tendencies towards it. Even more relevant is the choice to explicitly avoid the modelling of large crises (that for someone is a motivation for not attacking pre-crisis DSGE models focused on the analysis of small deviations from the steady-state), so denying the intrinsic nature of capitalism, a system that necessarily proceeds through cycles and (extended) crises. The replies of the DSGE approach to critics have led to extensions regarding for instance the role of financial frictions, heterogeneous agents, and bounded rationality (though typically in the form of quasi-rational expectations). The alternative paradigm of Agent-Based Macroeconomics can take into account all these elements at once within an evolutionary modelling framework based on heterogeneity and interaction, so capable to endogenously reproduce complex dynamics, from small fluctuations to large crises, due to innovation and industrial dynamics, rising inequality and financial instability, and so on. The integration between Agent-Based Macroeconomics and the (post-Keynesian) Stock-Flow Consistent approach represents a promising way for the future development of this research field.
Keywords: 330